MOTIVASI KERJA KARYAWAN DI HOTEL GRAND TJOKRO PEKANBARU - Amelia, Riska; Achnes, Syofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research aimed about employee’s motivation at Grand Tjokro Hotel Pekanbaru. This research aims to: (1) to know about employee’s motivation. (2) to know the multi way to increase employee’s motivation at Grand Tjokro Hotel Pekanbaru.This research was used descriptive quantitatif method to describe the issues. The sample used in this research was 44 people.The results of this research indicate that based on the research results obtained on the employee motivation at Grand Tjokro Hotel Pekanbaru good enough. This is evidenced by the acquisition of the overall total score of internal factor and eksternal factor, which is 1.296 points.Keywords: Motivation, employee, internal factor, eksternal factor.